Case Studies as a Qualitative Research Method to Make Research Scientific - Jagad Aditya Dewantara (CV. Rayyan Dwi Bharata, 2022)
At present there is a wide range of research. A study referred to as case studies and what is also typical, students seemed the more confusion, so impressed choose case study as a research strategy just because it follows other friends, without sufficient understanding. As a result the final destination case studies to gain a deep knowledge about the theme or topic examined is not achieved, so that the research work was in vain. In fact, time, energy, thought, and has a lot of money spent on such activities. This paper will discuss about the concept and strategy of research case studies, so that research can be done effectively